Experimental and numerical study on ultimate strength of stiffened columns under axial compression. (1st December 2020) - Mei, Hongyuan; Wan, Qi; Wang, Deyu
Abstract: The ultimate strength of six stiffened columns under axial compressive loading are studied by experimental and numerical methods. The web local buckling mode observed in specimens is analyzed based on the measured strain and displacement during the test. The effects of measured stress-strain curve and elastic/perfectly plastic curve of material to the ultimate strength of specimens are investigated by numerical calculations. The simply supported boundaries at the loaded edges and free boundaries at unloaded edges were produced based on the horizontal test fixture. The initial geometrical imperfections were measured and tensile tests with different thicknesses were conducted to get the true stress-strain curve. The strain gauges and displacement meters were installed to analyze the failure modes and it indicated that the local web buckling occurred first and dominated the collapse. The ultimate strength calculated by numerical analysis reaches a good agreement with experimental results. The ultimate strength calculated with the elastic/perfectly plastic curve is approximately 10% larger than that with the true stress-strain curve. It indicates that the elastic/perfectly plastic material constitutive model will not always overestimate the ultimate strength as the non-linear property between the proportional limit stress and 0.2% proof stress of material would reduce the ultimate strength. Highlights: Web local buckling mode is observed and analyzed based on the measured strains and displacements in this test. The failure location of specimens under web local buckling collapse is not always in the middle of the longitudinal length. The elastic/perfectly plastic material model may overestimate the ultimate strength than the true material curve as the non-linear property between proportional limit stress and 0.2% proof stress of material would reduce the ultimate strength.